2018
DOI: 10.1111/bjir.12416
|View full text |Cite
|
Sign up to set email alerts
|

Women's Participation in a Radical Trade Union Movement That Claims to be Feminist

Abstract: This article investigates the under‐researched topic of women's representation in radical unions, drawing on an in‐depth case study of the French Solidaires, Unitaires et Démocratiques (SUD) movement. In addition to an overview of the institutional and organizational dynamics of unions’ ‘inequality regimes’, it offers a contextually grounded analysis of the barriers and enablers of women's participation in SUD unions. More specifically, this research reflects on the complex interrelationships between class and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 63 publications
1
7
0
1
Order By: Relevance
“…Inspiration can also be found in studies of gender in NPOs published in adjacent disciplinary-specific fields, such as sociology, gender studies, and organization studies. Here we find studies on how gender, intertwined with class and race, is (re)produced among, for example, workers in nonprofit social services (e.g., Baines et al, 2014Baines et al, , 2015; members and elected representatives in trade union contexts (e.g., Guillaume, 2018;Guillaume & Pochic, 2011;Kirton & Healy, 1999;Sayce et al, 2006); alternative, feminist and women's organizations (e.g., Ferree & Martin, 1995;Kleinman, 1996;Schwabenland et al, 2016;Spoor & Hoye, 2014); and, employees, leaders, elected representatives and volunteers in sports organizations (e.g., Baxter et al, 2021;Burton, 2015;Burton & Leberman, 2017;Hovden, 2006;Spoor & Hoye, 2014). In addition, nonprofit scholars could also draw on studies of diversity and inclusion in NPOs that are based on theories related to gender in organizations (e.g., Bradshaw & Fredette, 2013;Fredette et al, 2016;Weisinger et al, 2016).…”
Section: An Acknowledgement Of Npos As Arenas In Which Gender Is (Re)...mentioning
confidence: 98%
“…Inspiration can also be found in studies of gender in NPOs published in adjacent disciplinary-specific fields, such as sociology, gender studies, and organization studies. Here we find studies on how gender, intertwined with class and race, is (re)produced among, for example, workers in nonprofit social services (e.g., Baines et al, 2014Baines et al, , 2015; members and elected representatives in trade union contexts (e.g., Guillaume, 2018;Guillaume & Pochic, 2011;Kirton & Healy, 1999;Sayce et al, 2006); alternative, feminist and women's organizations (e.g., Ferree & Martin, 1995;Kleinman, 1996;Schwabenland et al, 2016;Spoor & Hoye, 2014); and, employees, leaders, elected representatives and volunteers in sports organizations (e.g., Baxter et al, 2021;Burton, 2015;Burton & Leberman, 2017;Hovden, 2006;Spoor & Hoye, 2014). In addition, nonprofit scholars could also draw on studies of diversity and inclusion in NPOs that are based on theories related to gender in organizations (e.g., Bradshaw & Fredette, 2013;Fredette et al, 2016;Weisinger et al, 2016).…”
Section: An Acknowledgement Of Npos As Arenas In Which Gender Is (Re)...mentioning
confidence: 98%
“…However even an implicit commitment to feminist frameworks has had mixed outcomes. In her study of a feminist-identified Trade Union in France, Guillaume (2018) found it exhibited less hierarchy and incubated feminist consciousness among its members. However, it did not escape the enduring centrality of class in framing union struggle nor a lack of gender parity in senior decision roles.…”
Section: Methodsmentioning
confidence: 99%
“…Along the same lines, union participation may be constrained by a hostile industrial relations climate that creates insecurity (Hu et al, 2018; Kirton, 2018) or by an intensification of professional work (Gavin et al, 2022; Kirton, 2018). Additionally, research has demonstrated that women are less “biographical available for activism” in unions because of their family situation and the dominant culture that assigns care-giving tasks preferentially to women (Guillaume, 2018: 574).…”
Section: From the Individual To The Ir System: The Conceptual Frameworkmentioning
confidence: 99%